findjob helping high school graduates to find a job in the BPO industry - Fabian, John Neil R.; Dans, Sandra Michelle (Quezon City College of Fine Arts, University of the Philippines Diliman, 2024)
The purpose of this research is to help high school graduates to find a job in the BPO Industry. The number one reason why high school graduates stop their studies is because of financial problems. Because of that, they are having a hard time looking for a stable job, a job that can sustain their needs and wants. Through this research, the researcher came up with a design problem which is "how can I help high school graduates to find a job in the BPO Industry around Metro Manila." The researcher choose to recommend BPO jobs because it offers a good salary, benefits and they accept high school graduates and that is a good start and opportunity for high school graduates.

The researcher made an application called findjob, it is an app for searching BPO jobs. All of the users of findjob have an access to write their referrals that can be an extra income for them and it has a feature of a grab voucher that can solve the problem of many high school graduate in terms of looking for a job which is their transportation to their scheduled interviews.

Through the user testing, a lot of opportunities to improve the app has been discovered, and there are suggestions that cannot be done because of the limitations of the research. The focus is more on online job searching that are only for BPO jobs, that might help the future researcher to think on other things that can be helpful for other high school graduates.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 41-45
Keywords: Job hunting; Job hunting -- Students; Job vacancies -- BPO industry; BPO Indsutry